Psychological Motivational Profile of a Serial Killer “Mercy-Hero” vs. Power/Control Type - Soria, Miguel Ángel; Ansa, Nerea (Journal of Psychology and Psychotherapy Research, 2016)
On October 2010, the death of an elderly woman in a geriatric residence in the province of Girona (Catalonia), launched a police investigation, which ended up with the confession of eleven murders committed by one employee, Joan Vila Dilme (JVD). The killings were committed between August 2009 and October 2010; the eleven victims were elderly people between 80 and 96 years old, who lived in the residence. The employee administered to the victims a mixture of psychotropic drugs, insulin and caustic products. Different multidisciplinary teams evaluated, with forensic assessment proposed, the offender mental state and his biographic and personality background focused on a clinical-pathological vs. psychosocial-criminological perspective. Although he always claimed that his primary motive was to help those people he loved to stop suffering. On June 2013 he was condemned to one hundred and twenty-seven and a half years in prison, becoming the most prolific serial killer in Spain on the current century, and the fourth for sixty years before. The goal of this article is to analyse in depth this particular case, which provoked a strong media effect, highlighting the psychological factors regarding the offender motivation, his psychobiography background and his mental state.